Triple Canal Occlusion for the Treatment of Intractable Menière's Disease. Issue 1 (January 2021) - Gill, Charn; Muzaffar, Jameel; Kumar, Raghu; Irving, Richard
Abstract : Objective: Menière's disease can be a debilitating condition but in most cases the symptoms are controlled by lifestyle changes and medical management. However, some patients remain symptomatic despite medical treatment and have the option of more invasive surgical treatments. Surgical intervention for Menière's includes a range of interventions from grommet insertion, intratympanic steroids/Gentamicin, endolymphatic sac decompression, labyrinthectomy, and vestibular neurectomy. A recently described technique involves the occlusion of all three semi-circular canals as an alternative in intractable Menière's disease. Study Design: This is a case series of three patients who underwent triple canal occlusion for the treatment of intractable Menière's disease. Setting: Patients were selected from those who were referred to Queen Elizabeth Hospital in Birmingham, a tertiary referral center. Patients: Patients who were severely symptomatic despite medical treatment who were considering ablative therapy were offered the option of triple canal occlusion as an alternative. Intervention: We report a series of Menière's patients treated by triple canal occlusion, describe the rationale behind this intervention, the surgical technique, and preliminary results. Main Outcome Measure: Each patient was followed up for a minimum of 2 years following the procedure. The main outcomes measures were the class of vertigo control and hearing threshold levels according to the American Academy of Otolaryngology–Head and Neck Surgery guidelines. Results: Of the three patients, two were men and one was woman, the age range was 45 years to 61 years old. Two patients with unilateral disease achieved class A control whereas one patient with bilateral disease achieved class B control. Two patients who underwent the procedure had little or no effect to their hearing on the treated side however one patient suffered a 30 dB hearing loss on the operative side. Conclusions: Based on our limited experience and the early reports in the literature we consider that there are potential patient benefits for triple canal occlusion for intractable Menière's disease as an alternative to vestibular neurectomy due to the reduced morbidity and long-term efficacy.